2007
DOI: 10.1038/sj.clpt.6100336
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Melphalan and Glutathione S-transferase Polymorphisms in Relation to Side Effects

Abstract: Melphalan is associated with severe side effects such as mucositis, diarrhea, and myelosuppression. We investigated how much the individual severity of these side effects is predicted by pharmacokinetics. In addition, we studied glutathione S-transferase GSTM1, GSTT1, and GSTP1 polymorphisms in relation to adverse events. A high interindividual pharmacokinetic variability was observed in 84 patients. There was a linear correlation between creatinine and melphalan clearance (P=0.0004). Patients treated with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 26 publications
3
33
0
2
Order By: Relevance
“…29,30 Indeed, a recent study by a German group found that patients treated with a melphalan dose X70 mg/m 2 had a 23-fold increased risk of developing mucositis (Po0.001) compared with those receiving lower doses. 30 Thus, we tentatively evaluated whether there was an association between melphalan dose per kg body weight and medical resource use, in MM patients only. No relationship was found, indicating that the observed associations of OM with medical resource use were not directly on account of higher drug doses.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Indeed, a recent study by a German group found that patients treated with a melphalan dose X70 mg/m 2 had a 23-fold increased risk of developing mucositis (Po0.001) compared with those receiving lower doses. 30 Thus, we tentatively evaluated whether there was an association between melphalan dose per kg body weight and medical resource use, in MM patients only. No relationship was found, indicating that the observed associations of OM with medical resource use were not directly on account of higher drug doses.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that it was possible to recover more than 60% of the dose in three (of nine) patients in one study suggests that renal excretion is likely to be the major elimination pathway for melphalan. 12 Population PK analyses have also identified renal function as a significant determinant of melphalan clearance, 14,15 with renal clearance estimated to be approximately 40%. 15 …”
Section: Melphalan Eliminationmentioning
confidence: 99%
“…12 Population PK analyses have also identified renal function as a significant determinant of melphalan clearance, 14,15 with renal clearance estimated to be approximately 40%. 15 …”
Section: Melphalan Eliminationmentioning
confidence: 99%
See 2 more Smart Citations